PENGARUH CURRENT RATIO (CR) DAN RETURN ON ASSET (ROA) TERHADAP PRICE TO BOOK VALUE (PBV) PADA PT ULTRAJAYA MILK INDUSTRY & TRADING COMPANY TBK PERIODE 2014-2023 - Angraeni; Asep Muhammad Lutfi (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the Current Ratio (CR) and Return On Asset (ROA) variables on Price To Book Value (PBV) at PT Ultrajaya Milk Industry & Trading Company Tbk for the 2014-2023 period. This research method is descriptive quantitative. The data analysis technique used is linear data regression with a 10 (ten) year time series, namely the 2014-2023 period and at PT Ultrajaya Milk Industry & Trading Company Tbk. Based on the results of the partial test (T test) Current Ratio (CR), the T value was -0.857 with a significance of 0.420. Because Tcount < Ttable (-0.857 <1.89458) and the significance value > significant level (0.420> 0.05). So the conclusion is that the Current Ratio (CR) has no effect on Price To Book Value (PBV). The results of the research for Return On Asset (ROA), obtained a T value of -0.349 with a significance of 0.737. Because Tcount < Ttable (- 0.349 < 1.89458) and the significance value > significant level (0.737 > 0.05). So the conclusion is that Return On Asset (ROA) has no effect on Price To Book Value (PBV). The results of simultaneous hypothesis testing (F test) can be seen that the Fcount value is 0.657, which is smaller than the Ftable of 4.74 or 0.657 < 4.74, while the significance value of 0.548 is greater than 0.05 or 0.548 > 0.05, so this is it can be concluded that the Current Ratio (CR) and Return On Asset (ROA) simultaneously have no effect on Price To Book Value (PBV).